2020
DOI: 10.22271/phyto.2020.v9.i6b.12869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pollen source on some fruit characteristics of exotic pear (Pyrus communis L.) cv. carmen and abate Fetel

Abstract: A research experiment was conducted on two fruit bearing exotic cultivars "Carmen" and "Abate Fetel" of pear (Pyrus communis L.). The treatments included self, open and cross pollination of these two maternal parents with seven pollinizers viz., "William Bartlett", "Fertility", "Clapp's Favourite", "Chinese Sandy Pear", "Max Red Bartlett", "Kings Pear" and "Beurre de Amanalis". The design of experiment was RCBD with three replications and the number of treatment combinations were 18. Pollen source affected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Most pears are self-incompatible fruits with obvious xenia, and the fruit quality is affected by the source of pollination. The effect of pollination source can be seen in attributes such as fruit hardness and sugar, acid, vitamin C, and SCC contents ( Cai et al., 2010 ; Cheng et al., 2020 ; Mumtaz et al., 2020 ). We previously pollinated ‘Dangshan Su’ with pollen from two different varieties of pears and found that pollen from different parents significantly affected the expression of microRNAs and proteins related to lignin metabolism in pear fruit ( Cheng et al., 2017 ; Li et al., 2018 ), thus affecting lignin deposition, which in turn affected stone cell formation in pear fruit and ultimately the taste of pear fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Most pears are self-incompatible fruits with obvious xenia, and the fruit quality is affected by the source of pollination. The effect of pollination source can be seen in attributes such as fruit hardness and sugar, acid, vitamin C, and SCC contents ( Cai et al., 2010 ; Cheng et al., 2020 ; Mumtaz et al., 2020 ). We previously pollinated ‘Dangshan Su’ with pollen from two different varieties of pears and found that pollen from different parents significantly affected the expression of microRNAs and proteins related to lignin metabolism in pear fruit ( Cheng et al., 2017 ; Li et al., 2018 ), thus affecting lignin deposition, which in turn affected stone cell formation in pear fruit and ultimately the taste of pear fruit.…”
Section: Introductionmentioning
confidence: 99%